The Most Commonly Mispronounced Words in English (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines the pronunciation errors encountered by Uzbek learners of English and provides assistance in correcting these errors. Additionally, it offers the correct pronunciation of words in both British and American English speaking styles, presenting these pronunciations both in phonetic transcriptions and in a form that is easily understandable to the learner using regular letters.